Teachers’ use of creativity in teaching visual art in senior secondary school in Ilorin West LGA, Kwara State - Ahmed, Kareem, I. (Kashere Journal of Education, 2023)
The study is designed to determine the teachers’ use of creativity in teaching visual art in senior secondary schools in Ilorin West LGA, Kwara State. Descriptive survey research design was used for the study. The population for the study comprised all secondary schools in Kwara state. The sample consisted of one hundred and twenty-six (126) subjects. Purposive sampling technique was used to select all the subjects from 32 senior secondary schools in Ilorin West LGA, Kwara state as sample size of the study. Two instruments on Teachers’ Creativity in Teaching Visual Art (TCTVA), one from students’ responses and the other for the teachers’ responses were developed by the researcher and used to collect the data. Each item of both questionnaires measured the same variable. Four Educational Technology experts with Fine Art background from University of Ilorin validated the instrument for face and content validity. Pearson Product Moment Correlation statistics was used to test reliability of the instruments. Reliability coefficients of 0.88 and 0.74 were obtained for teachers and students questionnaire respectively. Three research questions were raised and two research hypotheses were formulated and tested using t-test at 0.05 level of significant. The result revealed that the originality and adaptation in creativity were rarely used by visual art teachers. Teachers’ mean shows that they used fluency and motivation in creativity sometime. There was significant difference between male and female visual art teachers in the use of creativity. Also, there was significant difference between qualified and unqualified visual art teachers in the use of creativity in teaching visual art. Based on the findings of this study, it was recommended among others that visual art teachers should try to improve on their creativity for effective teaching visual art.